1999
DOI: 10.1046/j.1469-7580.1999.19540551.x
|View full text |Cite
|
Sign up to set email alerts
|

Scoring of nonmetric cranial traits: a population study

Abstract: The aims of the present study were : (1) to supply further knowledge about variations in nonmetric cranial traits in relation to sex, age and laterality and (2) to evaluate biological distance between samples from a recent population. The incidence of 18 nonmetric variants of the cranium were determined in 3 adult samples of 394 skulls of known sex from North Sardinia (Sassari, Alghero and Ozieri) ; for the Sassari sample (n l 200) age at death was also known. Some significant sex differences were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
4
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
2
15
4
2
Order By: Relevance
“…The reason for the presence of wormian bones at Lambda may be that the interparietal part of the squamous occipital bone and the highest nuchal lines develops in membrane, usually from two pairs of ossification centres [33]. After reviewing the table-2 the present study is in acceptance that the presence of wormian bones is very rare at Bregma which correlates with the previous studies done by Brasilli P et al [34] and Manjula patil et al [35].…”
Section: Resultssupporting
confidence: 80%
“…The reason for the presence of wormian bones at Lambda may be that the interparietal part of the squamous occipital bone and the highest nuchal lines develops in membrane, usually from two pairs of ossification centres [33]. After reviewing the table-2 the present study is in acceptance that the presence of wormian bones is very rare at Bregma which correlates with the previous studies done by Brasilli P et al [34] and Manjula patil et al [35].…”
Section: Resultssupporting
confidence: 80%
“…Ossenberg (1970) suggested that pooling to increase sample size was appropriate in many cases because age, sex, and side differences tend to be small. However, other researchers dispute this, and the reported strength of these effects varies for different populations (Hauser and De Stefano, 1989;Brasili et al, 1999). We did not find differences in ossicle expression among the three age groups, but even with a large age range that included all subadults \19 years, our sample sizes for the youngest age group were small.…”
Section: Discussioncontrasting
confidence: 78%
“…Given the large number of comparisons utilized to test age and sex differences and the small available subsample sizes, particularly for males, our significant results could be due to random sampling error. In their review of the literature, Brasili et al (1999) found that sex bias in the expression of lambdoid ossicles varied across populations, so our findings are neither consistent nor inconsistent with the results of other studies. However, right lambdoid sutural ossicles are not just more frequent in undeformed males in comparison to females, but also in comparison to deformed males, providing further evidence of an anomalously high value in this particular subsample.…”
Section: Discussioncontrasting
confidence: 76%
“…0.4 % has been reported in North Indian population, 1.32 % in Central India, and 14 % in a South Indian population (Singh et al 1979;Marathe et al 2010;Murlimanju et al 2011). Elsewhere in the world, an incidence of 2.9-4.6 % has been reported in an American population of the south west coast, whereas an incidence of 57 % was observed in an Italian population of North Sardinia (Berry and Berry 1967;Brasili et al 1999). Hanihara and Ishida studied the frequency of Inca bones among major human populations in the world and reported significant regional variations.…”
Section: Discussionmentioning
confidence: 96%